Pengolahan Limbah Cair Industri Karet Dengan Kombinasi Proses Pretreatment Dan Membran Ultrafiltrasi - Windy Nila Hakim; Jhon Armedi Pinem; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The development of new industries can increase prosperity for the people, but had a negative impact on the environment. Industries that produce waste one of them is the rubber industry. Rubber industries produce wastewater containing organic compounds are relatively high. Rubber industrial wastewater treatment needs to be done first in order to tackle pollution. This study was conducted to test the effectiveness and influence of pretreatment process and ultrafiltration membranes in wastewater treatment process of the rubber industry. Wastewater rubber which has been neutralized, in coagulation using coagulant aluminum sulfate (150 mg/l; 200 mg/l; 250 mg/l) with stirring speed of 200 rpm for 5 minutes and 60 rpm for 15 minutes, then allowed to stand for 30 minutes. Waste water sample is filtered then ultrafiltration with variations in pumping pressure (1 bar, 1,5 bar, 2 bar). The results showed the coagulation process is effective at a dose of coagulant Aluminum Sulfate 250 mg/l is 58,71% of BOD5, 59,04% of COD, 35,71% of TSS and 25% of ammonia. The percentage of waste generated rejection increases with increasing pumping pressure of 1 bar to 2 bar. The rejection percentage is 67,30% of BOD5, 67,19% of COD, 88,15% of TSS and 35,71% of ammonia at 2 bar.Key Words: Aluminium sulfate, coagulation, wastewater rubber, membranes, pressure, ultrafiltration